Just Evil Enough The Subversive Marketing Handbook - Croll, Alistair (Volcanic Press, 2025)
Looking for an advantage in an unfair world? The rules of poker tell you how to play--but not how to win. You win by bluffing, looking for your opponent's tells, remembering cards, and intimidation. So why is it that in business we spend so much time teaching the rules, and so little finding new ways to win? For the last decade, expert in strategic communications Emily Ross and bestselling business author Alistair Croll have studied hundreds of brands, start-ups, leaders, and activists that employed an unfair advantage to conquer their competition. Here they offer an insight into their innovative go-to-market strategy in an attention economy that they call Just Evil Enough. Packed with fascinating case studies that will inspire your inner supervillain, Just Evil Enough includes practical frameworks like the Recon Canvas and the Long Funnel, along with eleven fundamental tactics such as Reframing, Bait-and-Switch, and Misappropriation that show up time and again when underdogs challenge the status quo and reinvent their industries. Revealing the secrets and mindset of some of the best subversive marketers in the business, Just Evil Enough is the essential handbook for anyone who wants to cut through the noise and stride ahead in the attention economy